METAPHOR IN SIA’S SONG - Emily Sukma Dara Damanik, Elza Fauziah Harahap, Riski Amanah, Siti Rahma Rambe (Lembaga Penelitian dan Pengabdian Masyarakat, 2022)
The focus of this research is on Methapor in Sia’s song. The qualitative research approach used in this publication is the collection of Sia’s song. The researchers used 4 Sia’s song to collect the data of Metaphor. Following the collection and slection data, the researher analysize the lyric using the Metaphor raltion theory of Semantic. Based on data findings, it is concluded that by understanding the source about Metaphor, and the researcher have a better and improved understanding in interpreting Metaphor in other word, the research amd reader understanding of the Metaphor’s intended meaning improves.